Pancasila dalam Moderasi Beragama: Membaca Ruang Media Komisi Komunikasi Sosial Keuskupan Agung Semarang - Nurrohmah, Shinta; Aris Yusuf, Mochamad; Aditya Putra, Robby (Journal of Da'wah, 2022)
One of the pillars of Pancasila which reads "Belief in One Almighty God" is used by the Semarang Archdiocese's Social Communication Commission as coercion in religious moderation in the media space. Even though religious moderation is often declared by certain Muslim activists. So this article aims to find out how this community builds religious moderation in the media space. The method used in this study uses a qualitative descriptive method with the data source, namely the Komsos Archdiocese of Semarang youtube channel. Data obtained through observation, interviews, and documentation related to research. The results in this study are that the Semarang Archdiocese's Komsos youtube channel has used the four pillars of religious moderation, namely; National Commitment with the acceptance of Pancasila as the state ideology. Tolerance, an attitude that is very necessary in society in order to bring about peace. Anti-violence, encouraging every religious community to avoid violence. Accommodating to local culture is an attitude that reflects an ability, but in this pillar the practice is not optimal.